Predictors of contrast-induced nephropathy in ST-elevation myocardial infarction patients undergoing primary percutaneous coronary intervention - Mohamed Abdel-Ghany; Ghada Morsy; Yehia Taha Kishk (SpringerOpen, 2021)
Abstract Background Contrast-induced nephropathy (CIN) is a serious complication with primary percutaneous coronary intervention (PPCI). We aimed to study the different predictors of CIN and determine the cutoff point of contrast volume (CV)/creatinine clearance (CrCl) and the applicability of CHA2DS2-VASC score in the prediction of CIN after PPCI in ST-elevation myocardial infarction (STEMI) patients. Four hundred patients presented with STEMI and eligible for primary PCI were included in the study. Patients with GFR < 30 ml/min were excluded from the study. Results Fifty-four (13.5%) patients who developed CIN who were older (64.20 ± 13.16 vs. 55.80 ± 10.58) had a higher prevalence of diabetes mellitus (DM), hypertension (HTN), and female gender than those without CIN. They also had a higher Killip class and lower hemoglobin (HB) level (P < 0.05) compared to those with no CIN. The incidence of no CIN was (85.8%) in the low-risk Mehran score group and 14.2% in the moderate-risk group, and all patients of high and very high score group developed CIN (P<0.001). Multiple logistic regression showed that old age (OR= 1.06, 95% CI= 1.02-1.11, P< 0.001), female sex (OR= 3.1, 95% CI= 2.65-6.99, P= 0.02), high Mehran score (OR=2.48, 95% CI= 1.98-6.24, P= 0.01), CV/CrCl > 2.8 (odds ratio=1.45, 95% CI= 1.22-2.01, P= 0.03), and CHA2DS2-VASC score > 2 (odds ratio=1.90, 95% CI= 1.76-2.11, P= 0.04) were predictors of CIN. Conclusions Old age, female sex, high Mehran score, CHADS2-VASC score > 2, CV/CrCl > 2.8 were predictors of CIN in STEMI patients who underwent PPCI.